SURVAI DASAR GIZI DAN KESEHATAN DI WILAYAH KERJA WORLD VISION INDONESIA DAN WAHANA VISI INDONESIA DI KABUPATEN MERAUKE - Lindawati Wibowo; Otte Santika; Markus Puthut Harmiko (Jurnal Gizi dan Pangan, 2012)
This survey was conducted to estimate levels of health and nutrition problems as well as the associated factorsamong under-five children in the Area Development Program of World Vision Indonesia and Wahana Visi Indonesia in Merauke district. As many as 30 Posyandus were randomly selected as the cluster units where the information was collected among children U-5 and their mothers (n=542). From this survey we estimated the prevalence of underweight, stunted, wasted, and anemic children were 11.7%, 21.0%, 7.5%, and 73.7% respectively. It was assumed that these nutritional problems were associated with several factors such as: family income, mother’s literacy, knowledge and practices of mothers on health and nutrition, as well as the existing nutrition and health program implementation. This survey concluded that the nutrition problems in the study site were categorized as a public health concern. Thus, as the recommendations, two strategies to alleviate the local nutrition and health problems were proposed: direct and indirect. The direct approach is mainly focus on the improvement of existing nutrition and health programs (i.e. GMP, high dose vitamin A program, promotion of proper child feeding, etc.) implementation. Prior to that, a health system review must be carried out to identify the presence and functioning of the essential system components. Indirectly, a program need also to be carried out through multisectoral and community participation based on the government’s leadership for the sake of alleviating poverty and illiteracy as the major underlying factors of malnutrition.Key words: malnutrition, children underfive years, anemia, quality of heath service, MeraukeABSTRAKPenelitian ini bertujuan untuk menilai besaran masalah gizi dan kesehatan serta faktor-faktor yang mempengaruhinyadi wilayah kerja World Vision Indonesia dan Wahana Visi Indonesia di Merauke. Sebanyak 30 posyandu dipilih acak sebagai unit klaster. Pengumpulan data dilakukan pada ibu balita (n=542) di unit klaster terpilih. Hasil penelitian menunjukkan estimasi prevalensi balita dengan berat badan kurang, pendek, kurus, serta menderita anemia berturut-turut adalah 11.7%, 21.0%, 7.5% dan 73.7%. Masalah ini diasumsikan terkait dengan beberapa faktor seperti: pendapatan keluarga, tingkat literasi pengasuh, pengetahuan dan praktik pengasuh yang berkaitan dengan gizi dan kesehatan, serta implementasi program gizi dan kesehatan. Penelitianini menyimpulkan bahwa kasus kurang gizi masih tergolong permasalahan kesehatan masyarakat. Sebagai rekomendasi, disarankan untuk menjalankan dua strategi secara paralel yaitu 1) dengan mengoptimalkan program-program yang sudah berjalan seperti pemantauan status gizi di posyandu, program suplementasi vitamin A, pencegahan dan pengendalian penyakit, dan promosi pemberian ASI dan MP ASI dengan didahului oleh review sistem kesehatan agar diketahui komponen sistem yang mana yang perlu penguatan, 2) melalui kerjasama lintas sektor dan melibatkan partisipasi masyarakat bersama-sama dengan pemerintah untuk mengentaskankemiskinan dan iliterasi yang menjadi akar permasalahan kasus kurang gizi.